2014
DOI: 10.1111/all.12413
|View full text |Cite
|
Sign up to set email alerts
|

Is chronic rhinosinusitis related to allergic rhinitis in adults and children? Applying epidemiological guidelines for causation

Abstract: The relationship between allergic rhinitis and chronic rhinosinusitis has been assessed in a number of observational and experimental studies. In this review, we attempt their synthesis and evaluation using the modified Bradford Hill guidelines for causation. Although there is no proof of causation, especially in the pediatric literature, an evaluation of underlying allergies is recommended at least as an initial measure of symptoms relief.Chronic inflammatory disorders of the upper airways are extremely preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 70 publications
(68 reference statements)
0
25
0
Order By: Relevance
“…CRS is generally classified under the following 2 subtypes: CRS with nasal polyps (CRSwNP) and CRS without nasal polyps (CRSsNP) [2]. Although CRSwNP and CRSsNP have the same clinical presentation and symptoms, it appears that they are characterized by distinct pathophysiological mechanisms [3]. CRSsNP shows Th1 polarization with high levels of interferon-γ (IFN-c) and transforming growth factor-β (TGF-b), whereas CRSwNP is characterized by Th2 polarization with high IL-5 and immunoglobulin E concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…CRS is generally classified under the following 2 subtypes: CRS with nasal polyps (CRSwNP) and CRS without nasal polyps (CRSsNP) [2]. Although CRSwNP and CRSsNP have the same clinical presentation and symptoms, it appears that they are characterized by distinct pathophysiological mechanisms [3]. CRSsNP shows Th1 polarization with high levels of interferon-γ (IFN-c) and transforming growth factor-β (TGF-b), whereas CRSwNP is characterized by Th2 polarization with high IL-5 and immunoglobulin E concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that AR may be a predisposing factor for development of CRS . If this is the case, it is possible that the degree of atopy, as measured by the number of aeroallergen sensitivities, may be associated with the development of CRS in patients with AR.…”
Section: Discussionmentioning
confidence: 99%
“…Based on common comorbidity, immunologic mediators and symptomatology, there exist reported epidemiologic and pathophysiologic links between allergic rhinitis (AR) and chronic rhinosinusitis (CRS) . In addition, AR has previously been associated with individuals who develop CRS .…”
mentioning
confidence: 99%
“…Co-morbidities were more common in patients with moderate/severe AR, with the highest rate for conjunctivitis, which was present in 54% of subjects, defining the picture of rhinoconjunctivitis, which occurs very frequently in patients with AR [21]. According with the literature, the other 2 most common co-morbidities were asthma (~38%) and sinusitis (~14%) [2226]. In treatment of AR, the most frequently used drugs were oral antihistamines (77%) and topical corticosteroids (61%), in accordance with the ARIA guidelines, which state the adequacy of these treatments based on the evidence from controlled trials [10,22].…”
Section: Discussionmentioning
confidence: 99%